Assessment of the Work Posture Risk Level of the Canting Process Batik Maker Based on the Rapid Entire Body Assessment (REBA) Method (Case Study: Batik Tulis Tengah Sawah Pacitan) - Valencia, Bella Renata; Astuti, Rahmaniyah Dwi; Pujiyanto, Eko (Faculty of Industrial Technology Universitas Islam Indonesia, 2024)
Batik Tulis Tengah Sawah is one of the UKM in Pacitan and is engaged in hand-written batik. In the production process, the batik maker makes the canting process while sitting on a short chair (dingklik) made of wood without a backrest. The stove used to melt malam is small and there is no table to put the stove on and it is used by 2 batik makers, so it requires the batik makers to sit obliquely facing the gawangan, causing the batik maker to sit with a slight bow. Therefore, it is necessary to assess the risk level of the work posture of the batik when doing the canting process. The purpose of this study is to evaluate the work posture of the batik maker during doing the canting process so that corrective action can be taken to reduce musculoskeletal complaints and bending posture. The result of this research is that the assessment of the risk level of the work posture of batik in all stages of the canting process activity has a REBA score of 5, which is included in the moderate or medium risk level with actions that need to be corrected.